2021
DOI: 10.1016/j.jpeds.2021.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Erythropoietin on Short- and Long-Term Kidney-Related Outcomes in Neonates of Extremely Low Gestational Age. Results of a Multicenter, Double-Blind, Placebo-Controlled Randomized Clinical Trial

Abstract: on behalf of the PENUT Trial Consortium* Objective To evaluate whether extremely low gestational age neonates (ELGANs) randomized to erythropoietin have better or worse kidney-related outcomes during hospitalization and at 22-26 months of corrected gestational age (cGA) compared with those randomized to placebo. Study designWe performed an ancillary study to a multicenter double-blind, placebo-controlled randomized clinical trial of erythropoietin in ELGANs. ResultsThe prevalence of severe (stage 2 or 3) acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…15 16 22 25 42 43 45 Askenazi et al found that at 22-26 months, approximately 330 (35.8%) of their 923 participants had a urine albumin/creatinine ratio greater than 30 mg/g. 45 Bacchetta et al found that 2 out of their 50 participants had moderate microalbuminuria at approximately 7 years of age. 25 Jones et al found that 2 out of their cohort of 28 premature had microalbuminuria at 4-5 years of age.…”
Section: Chronic Kidney Diseasementioning
confidence: 97%
See 4 more Smart Citations
“…15 16 22 25 42 43 45 Askenazi et al found that at 22-26 months, approximately 330 (35.8%) of their 923 participants had a urine albumin/creatinine ratio greater than 30 mg/g. 45 Bacchetta et al found that 2 out of their 50 participants had moderate microalbuminuria at approximately 7 years of age. 25 Jones et al found that 2 out of their cohort of 28 premature had microalbuminuria at 4-5 years of age.…”
Section: Chronic Kidney Diseasementioning
confidence: 97%
“…Studies that found a significant difference in GFR between groups Studies that did not find a significant difference in GFR between groups Askenazi et al 45 Open access…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 3 more Smart Citations